(untitled) (Revista Apotheke, 2018)
This text deals with discoveries and possibilities of pictorial materials from the analysis of the Assunção Gonçalves creation processes, artist and teacher from the city of Juazeiro do Norte / CE. The aim of this study is to democratize education of painting in discovery for new materials and pictorial techniques accessible to all, and instigating students of Visual Arts to search for materials and painting techniques in the region in which they operate. The research process is still ongoing, the results of experienced experiments until this moment have promoted an awakening to my pictorial production process in the discovery of the use of new materials and techniques, such as the use of the dye extracted from tissue paper, their optical effects and color combinations in painting and the transfer of photographic images of Assunção Gonçalves in their daily chores, to the canvas. The breakdown of these results will be worked in the classes of painting workshop with the students of Degree Course in Visual Arts at URCA, which I minister and later this study will be expanded in the Research Group on creation processes, which will be deployed in the Department of Visual Arts as a continuation of the research.